2019
DOI: 10.1088/1755-1315/301/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

The energy input-output analysis of maize production in Sundarharaincha Municipality, Morang district, Nepal

Abstract: Maize is the second largest crop grown in Nepal and is grown in all three geographic zones. The objective of this study is to analyse the energy input-output of maize production systems. The study is conducted in Sundarharaincha municipality of Morang district, Nepal, using direct questionnaires methods for the collection of primary data of varying landholding sizes farmers. The study revealed that total energy input and output for maize production system found about 10, 999.61 MJ/ha and 45, 501.52 MJ/ha, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The highest and the lowest energy required for producing a crop unit yield were 8.8 and 11.8 allocated to the first and the fifth methods, respectively. Planting with moldboard plow, roller and seed drill and minimum tillage system allocated 32.5% and 19% of total input energy to wheat production system [9]. It can be concluded from this research that minimum tillage lessened energy consumption in machinery and diesel fuel sectors; and since grain yield achieved in this method was not the lowest, its energy efficiency was higher than other seed bed preparation methods.…”
Section: Seed Bed Preparationmentioning
confidence: 80%
See 3 more Smart Citations
“…The highest and the lowest energy required for producing a crop unit yield were 8.8 and 11.8 allocated to the first and the fifth methods, respectively. Planting with moldboard plow, roller and seed drill and minimum tillage system allocated 32.5% and 19% of total input energy to wheat production system [9]. It can be concluded from this research that minimum tillage lessened energy consumption in machinery and diesel fuel sectors; and since grain yield achieved in this method was not the lowest, its energy efficiency was higher than other seed bed preparation methods.…”
Section: Seed Bed Preparationmentioning
confidence: 80%
“…▪ Energy consumption for crop planting: it includes all energy consumed for seed bed preparation, seed sowing, crop nutrition through application of fertilizers, crop protection by using pesticides and energy needed for plant harvesting (like human labor, machinery and diesel fuel) [1]. ▪ Energy consumption after crop harvesting: energy consumed for transporting, packaging and storage of agricultural products falls into this category [8,9].…”
Section: Of Energy Consumption In Agroecosystemmentioning
confidence: 99%
See 2 more Smart Citations
“…The study has concluded that the rice production via terai land and wheat production in a hilly region are more energy and environmentally efficient. A similar study also has been conducted for maize production in the eastern part of Nepal by Poudel et al in 2019(Poudel et al 2019, which estimated the energy use efficiency at a rate of 4.41.…”
Section: Introductionmentioning
confidence: 93%